Grants, Remittances, and the Equilibrium Real Exchange Rate in Sub-Saharan African Countries - Mongardini, Joannes (IMF Working Papers; Working Paper ;, 2009)
This paper builds on the methodology developed by Chudik and Mongardini (2007) to estimate the relationship between grants and remittances and the equilibrium real exchange rate in Sub-Saharan African (SSA) countries using panel techniques. The results indicate that grants and remittances are not associated, in the long run, with an appreciation of the real effective exchange in SSA and are therefore not likely to give rise to Dutch disease effects. These findings suggest that grants and remittances may be serving to ease supply constraints or boost productivity in the non-tradable sector in the recipient economies.